Interpersonal skills in organizations - De Janasz, Suzanne C.; Dowd, Karen O.; Schneider, Beth Z. (Dubuque, IA McGraw-Hill Education, 2019)
"Birth of an Idea While we were all teaching at James Madison University, a group of executives, who served as the College of Business dean's board of advisors at the university, identifi ed a critical ingredient missing in most business school graduates. The executives found that while students were technically competent--they could read a balance sheet, do a market analysis, and develop cash fl ow projections--many graduates lacked interpersonal skills or the ability to work effectively with others. The executives created a wish list of "soft skills," faculty were hired, and the Interpersonal Skills course was born. Since that time, thousands of students have taken part in this required undergraduate course. In the beginning, the cadre of faculty dedicated to this course selected two books and additional readings to support the course objectives. In response to student and recruiter feedback, we improved continuously both the content and delivery of the course. One such improvement stemmed from students' concerns that the books were inadequate for a variety of reasons. We agreed and continued to search for a book that met our needs. Frustrated with our inability to fi nd the interpersonal skills text for our particular audience, we decided to write it. As our colleagues and students have heard about this book, a common response is not simply "Where can I buy this book," but "My boss could use this--can you send him (or her) a copy?" The truth is this book is very relevant to a variety of readers. While it was written primarily with an undergraduate student audience in mind, each of the authors is experienced working with graduate students, adult learners, and working managers"--
"Interpersonal Skills in Organizations by de Janasz, Dowd, and Schneider takes a fresh, thoughtful look at the key skills necessary for personal and managerial success in organizations today. Exploding with exercises, cases, and group activities, the book employs an experiential approach suitable for all student audiences. The book is organized into 4 distinct sections (Understanding Yourself, Understanding Others, Understanding Teams, and Leading) that can be used collectively or modularly depending on the instructors' preferences and students' needs. The emphasis in this edition focuses on making the text more current along with making the text pedagogically effective for students and instructors"--
Includes index.
Revised edition of the authors' Interpersonal skills in organizations, [2015]
Keywords: Interpersonal relations; Organizational behavior; Psychology, Industrial